Trending Research Topics in the Field of Physics Education from 2017 to 2019 in Highly Reputable International Journals - Bancong, Hartono; Nurazmi, Nurazmi; Fiskawarni, Tri Hastiti; Park, Jisun (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
This study aims to map the physics education research topics trending in the last three years in highly reputable international journals. This is a descriptive study that analyzed 511 articles using content analysis. All articles were selected from the top 3 academic journals: International Journal of Science Education (IJSE), Research in Science Education (RISE), and Science Education (SE). All three journals have JSRs above 0.8 with a quartile of Q1. Data collection and analysis were carried out from April to September 2020. The results showed that the top research topics in the IJSE journal were science learning: contexts, characteristics, and interactions with a percentage of 15.05%. Likewise, in the RISE journal, the topics of science learning: contexts, characteristics, and interactions also ranked first with a percentage of 16.30%. Meanwhile, the top research topics in the SE journal were STEM/STEAM, with a percentage of 13.28%. Based on the results, it can be concluded that overall, the top three research topics highlighted by physics researchers in highly reputable international journals from 2017 to 2019 period were science learning: contexts, characteristics and interactions, STEM/STEAM, and curriculum and assessment.